2015
DOI: 10.5120/ijais2015451443
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Managing Information Flow in Nigeria Healthcare System

Abstract: The healthcare system is an information intensive domain that is responsible for capturing, processing and storing large volumes of health information which could be clinical, research or administrative in nature. Healthcare information is primarily used for making decisions, improving the efficiency and quality of healthcare systems as well as conducting research to enhance medical science in both developed and developing countries. Healthcare information is usually stored in paper form, physical files or dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…[16] To achieve an improvement in our discharge summary system, interventions which may be required include the following: intensive and regular physician education on discharge summary with provision for periodic group/individualized audit and feedback; need for the supervising consultants to oversee the preparing of these summaries on a regular basis; development of a standard curriculum for teaching medical students and junior doctors how to prepare discharge summaries; and development of validated standardized discharge summary templates which will recognize the peculiarities of specialized patient groups and suit our local context, as using such templates carry greater chances of achieving a completion rate close to 100% [17] and in line with global practices, transition to a computer-based electronic discharge summary system. [18] The Nigerian discharge summary system in many public hospitals is still basically part of a paper-based health information system; [19,20] which is the traditional format for writing discharge reports. Even in South Africa where appreciable efforts have been made to computerize the medical records system in many centers, the National Health Care Act still provides a broad scope of content and format for a discharge report as there is no universally adopted template or format.…”
Section: Discussionmentioning
confidence: 99%
“…[16] To achieve an improvement in our discharge summary system, interventions which may be required include the following: intensive and regular physician education on discharge summary with provision for periodic group/individualized audit and feedback; need for the supervising consultants to oversee the preparing of these summaries on a regular basis; development of a standard curriculum for teaching medical students and junior doctors how to prepare discharge summaries; and development of validated standardized discharge summary templates which will recognize the peculiarities of specialized patient groups and suit our local context, as using such templates carry greater chances of achieving a completion rate close to 100% [17] and in line with global practices, transition to a computer-based electronic discharge summary system. [18] The Nigerian discharge summary system in many public hospitals is still basically part of a paper-based health information system; [19,20] which is the traditional format for writing discharge reports. Even in South Africa where appreciable efforts have been made to computerize the medical records system in many centers, the National Health Care Act still provides a broad scope of content and format for a discharge report as there is no universally adopted template or format.…”
Section: Discussionmentioning
confidence: 99%
“…The proprietary systems relate to the HIS software or program used, made, or marketed by one having the exclusive legal right to it. Thus, the exchange of information and communication between health care service providers and health care practitioners is poor (Oluwaseun et al, 2015). The insertion of decision support tools in the Health Information System (HIS) is an advancement that has helped to greatly improve evidence-based decision making in many parts of the world today (Bates et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Nigerian healthcare system, data is mostly collected, processed, and stored in paper-based, legacy, and proprietary systems that are heterogeneously developed. Legacy systems are an old and outdated systems designed to meet hospital goals and needs from an earlier time and do not allow for interaction with newer systems (Oluwaseun et al, 2015). Though these systems have passed through many stages of historical development, including a series of policies and plans that various governing administrations have introduced and implemented (Sedenu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Meriboleet, et al (2014) noted in a study to review the policy that Nigeria's health information system is not delivering healthcare progress at the rate predicted. Olaronke et al (2013) found that only about four percent of general practising practitioners in Nigeria use IT applications for clinical purposes cited in the article on Interoperability in Nigeria Healthcare System. Ayangbekun and Oke (2014), in their study on comparative analysis of existing health information systems for the development of Nigerian Health Sector, found out that healthcare providers in Nigeria lack access to best-required technology skills and facilities to provide good services as a result of the challenges faced by the implementation of National Health Management Information System (NHMIS) among which are: inadequate funding, insufficient staffing, Shortage of infrastructure, poor coordination of data and workflow, epilepsy power supply and Huge backlog of unprocessed data, training, IT literacy among others.…”
mentioning
confidence: 99%